Temperament. Temperament Types - Shodmonova Dildora; Oymatova Dilorom Ro'zimurotovna (Euro Asian Journal Publishing, 2025)
This article presents a theoretical analysis of temperament and its types. Temperament is considered a key factor influencing a person's emotional, psychophysiological characteristics and activity speed. The author describes the classic types of temperament — sanguine, choleric, phlegmatic, and melancholic — and analyzes their psychological features. The article also discusses the significance of temperament in personality development and its application in modern psychological practice and education
Keywords: temperament; types of temperament